MAGICS. II. Seed Black Holes Stripped of Their Surrounding Stars Do Not Sink - Yihao Zhou; Diptajyoti Mukherjee; Nianyi Chen; Tiziana Di Matteo; Peter H. Johansson; Antti Rantala; Christian Partmann; Ugo Niccolò Di Carlo; Simeon Bird; Yueying Ni (The Astrophysical Journal)
Massive black hole (MBH) seed mergers are expected to be among the loudest sources of gravitational waves detected by the Laser Interferometer Space Antenna, providing a unique window into the birth and early growth of MBHs. We present the MAGICS-II simulation suite, which consists of six galaxy mergers that result in MBH seed mergers identified in the cosmological simulation ASTRID. With the enhanced resolution (mass resolution: 500 M _⊙ ; softening length: 5 pc), improved subgrid models for the MBH dynamics and accretion, and the accurate regularized gravity integrator included in KETJU, we trace MBH seed dynamics down to 0.1 pc. After evolving all the systems for  ≈1.2 Gyr in three stages (MAGICS-2000, MAGICS-500, and MAGICS-K), we find in four of the six systems that the MBHs stall at separations Δ r  ≳ 200 pc. Only in two systems, the MBHs manage to sink further, and only in one of them a bound binary forms. In the sinking systems, the MBH retains a population of bound stars. The final separation between the MBH is related to the surrounding unstripped stellar (and/or dark matter) mass: if more than 90% of the surrounding stellar system is stripped away, the MBHs stall. Besides the unstripped stars from the original host galaxy, we find that newly formed stars bound to the MBH significantly contribute to its sinking. Resolving the stellar system around MBH seeds, and its induced tidal interactions and dynamical friction is key for accurately capturing MBH dynamics. For this, high-resolution simulations are required. In a companion paper (MAGICS-III), we resimulate the central regions of these systems with an increased resolution to model directly the effects of actual star clusters around MBHs.